If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cos(3x + -20) = sin(5x + 6) Reorder the terms: cos(-20 + 3x) = sin(5x + 6) (-20 * cos + 3x * cos) = sin(5x + 6) (-20cos + 3cosx) = sin(5x + 6) Reorder the terms: -20cos + 3cosx = ins(6 + 5x) -20cos + 3cosx = (6 * ins + 5x * ins) -20cos + 3cosx = (6ins + 5insx) Solving -20cos + 3cosx = 6ins + 5insx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Reorder the terms: -20cos + 3cosx + -6ins + -5insx = 6ins + -6ins + 5insx + -5insx Combine like terms: 6ins + -6ins = 0 -20cos + 3cosx + -6ins + -5insx = 0 + 5insx + -5insx -20cos + 3cosx + -6ins + -5insx = 5insx + -5insx Combine like terms: 5insx + -5insx = 0 -20cos + 3cosx + -6ins + -5insx = 0 Factor out the Greatest Common Factor (GCF), 's'. s(-20co + 3cox + -6in + -5inx) = 0Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing c to the left, all other terms to the right. Add '-1s' to each side of the equation. s + -1s = 0 + -1s Remove the zero: 0 = -1s Simplifying 0 = -1s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-20co + 3cox + -6in + -5inx)' equal to zero and attempt to solve: Simplifying -20co + 3cox + -6in + -5inx = 0 Solving -20co + 3cox + -6in + -5inx = 0 Move all terms containing c to the left, all other terms to the right. Add '6in' to each side of the equation. -20co + 3cox + -6in + 6in + -5inx = 0 + 6in Combine like terms: -6in + 6in = 0 -20co + 3cox + 0 + -5inx = 0 + 6in -20co + 3cox + -5inx = 0 + 6in Remove the zero: -20co + 3cox + -5inx = 6in Add '5inx' to each side of the equation. -20co + 3cox + -5inx + 5inx = 6in + 5inx Combine like terms: -5inx + 5inx = 0 -20co + 3cox + 0 = 6in + 5inx -20co + 3cox = 6in + 5inx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| f-1=-3x^2+2x-7 | | 8q^2+4q=7q^2-2q+27 | | 13d+6=6d+27 | | 3(x-9)=-10.8 | | 3(x-9)=10.8 | | 7(a+5)=73.5 | | y-54=7t | | X^2+12x-9= | | 43.2=6c-9 | | an=15+3(n-3) | | 7e-1=15.8 | | -10x+9y=11 | | 6x^4-12x^3=0 | | 3p=29.1 | | h-25=36 | | 3k+2(3k+2)=49 | | 2x+12+38=80 | | 5v^2-11v-12=0 | | -5x+2y=-14 | | 0.66+1=4x-0.33 | | -4(n+7)-6n=-98 | | -5x-3=-20 | | 6n+8(n+3)=-2(2+2n)-8 | | 5=6w-9w-1 | | 16+3x+38=96 | | 16+3x+38+96=180 | | 7+4(1-4a)=-12+7a | | 5=6w-8w-1 | | x+0.1x=.017 | | 16x+3x+38=96 | | X^2+y^2+6X+2y+6=o | | -25=-10+1p |